THE EXISTENCE OF TRADITIONAL BLACKSMITHS ENTERING THE INDUSTRIAL REVOLUTION ERA IN SIDENRENG RAPPANG REGENCY - Cenceng Wadi; Ramli Umar; Ibrahim Abbas (UNM Geographic Journal, 2021)
The objectives of this study were: 1) To determine the working characteristics of traditional blacksmiths in Sidenreng Rappang Regency. 2) to find out what are the factors that influence the existence of traditional blacksmiths in facing the industrial era. 3) to find out how the traditional blacksmith survived in the industrial revolution era in Sidenreng Rappang district. The type of research used is descriptive quantitative research, which is used to describe the phenomenon of social reality found in people who are used as objects or targets in research that seeks to draw that reality to the surface as a feature, nature, character, sign, or description of the situation, situation. , model, or problem specific phenomenon. The results showed that the way blacksmiths survived in the industrial revolution era in Sidenreng Rappang district was by maintaining the distinctive form and resilience of the production of these goods, as well as having an affordable selling price, and availability in the area itself so that it was easily accessible to the surrounding community.